Purgailis – putns, augs vai pārpratums? - Bušs, Ojārs; Siliņa-Piņķe, Renāte (Baltistica, 2012)
Purgailis – A BIRD, A PLANT OR A MISUNDERSTANDING?SummaryPurgailis is a quite common Latvian surname, Purgaiļi is a frequently used place-name (mostly a name of a farmstead). The names are widely associated with Latv. purvs ‘a marsh’ and gailis ‘a cock’, however, in Latvian there is no common name *purgailis. The Estonian borrowing of the Baltic origin (soo)kail ‘Ledum palustre’ (cf. Est. soo ‘a marsh’) and the calque sookikas ‘id.’ (cf. Est. kikas ‘a cock’) is a result of the Latvian linguistic influence (although cf. Lith. gailiai ‘Ledum palustre’), thus there is a real possibility that Latvian might have had (a quite long time ago) a common name *purgaiļi ‘Ledum palustre’.